Lone stars - Lupica, Mike (2017)
When Coach Coop, a former star player for the Dallas Cowboys, starts exhibiting side effects from the many concussions he suffered while playing professionally, twelve-year-old wide receiver Clay Hollis becomes determined to help him get through the football season until Thanksgiving, when Coach plans to attend a ceremony honoring him and his former Super Bowl-winning teammates.
Keywords: Football -- Fiction; Coaches (Athletics) -- Fiction; Brain -- Concussion -- Fiction; JUVENILE FICTION / Sports & Recreation / Football; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance.; JUVENILE FICTION / Health & Daily Living / Diseases, Illnesses & Injuries; Texas -- Fiction